Tender is the night - Stern, Milton R. (Twayne Publishers, 1994)
Provides in-depth analysis of the literary work Tender is the Night, as well as its importance and critical reception. Includes a chronology of the life and works of the author
Description based on print version record
Keywords: Fitzgerald; F. Scott; Tender is the night